Institutional approach for the management of patients in orthodontic office during COVID-19 pandemic - Lakshman Chowdary Basam; Revathi Peddu; Sravanthi Tamineedi; Ram Chowdary Basam (Wolters Kluwer Medknow Publications, 2020)
COVID-19, the current pandemic has created a fearful scenario for health-care professionals. Being the frontline warriors, we need to have sound knowledge about the transmission of SARS-CoV-2 and protect ourselves during this pandemic. According to the published literature, ins pite of following possible precautionary measures against transmission of disease, there is an increased number of infected health-care workers with COVID-19. The purpose of this review is to provide the information for the postgraduates, faculties, orthodontic practitioners, and to some extent, guidance on possible transmission routes, patient assessment, laboratory investigations, various radiographic imaging techniques, proper disinfectant protocol in handling the patients, orthodontic emergency management, and elective orthodontic treatment.